Integrated analysis of transcriptomic and physiological responses to cold stress in Macrobrachium rosenbergii - Jiongying Yu; Shaokui Yi; Guoliang Yang; Weimin Wang (Aquaculture Reports, 2024)
The giant freshwater prawn (GFP), Macrobrachium rosenbergii, stands out as a vital species in freshwater shrimp aquaculture. However, its susceptibility to cold conditions has increased the cost of aquaculture and limited the growth of GFP cultivation. To furnish insights at the molecular level to enhance GFP's cold tolerance, transcriptome sequencing and physiological analysis of the hepatopancreas were performed in our study. Initially, we identified 4909 differentially expressed genes (DEGs) between experimental (15 °C, 24 h) and control groups (25 °C, 24 h). These DEGs were significantly enriched in the proteasome, spliceosome, lysosome, peroxisome, and lipid metabolism-related pathways including glycerolipid metabolism, sphingolipid metabolism, linoleic acid metabolism as well as steroid hormone biosynthesis. Histological examination following various stress durations revealed a notable increase in hepatocyte vacuoles after 6 h of cold stress. Hepatocyte structure deterioration occurred in the later phase (48 h), coinciding with a significant increase in cell apoptosis. Subsequent analyses demonstrated an initial increase followed by a decrease in superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH) content, while malonaldehyde (MDA) content rose with stress duration. Furthermore, a significant increase in triglyceride content and no significant change in cholesterol content was observed. RT-qPCR results unveiled significant down-regulated expression of FAS, TAGL, ACOX1, ACS and significant up-regulated expression of GPAT and DEGS. These findings suggest that oxidative stress and impaired lipid metabolism underlie the poor cold tolerance of GFP.